KONSEP MAQASHID SYARIAH DAN IMPLIKASINYA PADA PENDIDIKAN ISLAM - Miftahul Huda; Nurwadjah Ahmad; Andewi Suhartini (Universitas Islam Nahdlatul Ulama Jepara, 2022)
In the concept of maqashid shari'ah, it is explained regarding the urgency of maintaining the elements that exist in humans, both physical and spiritual in nature to be able to achieve benefit, which is also in line with the goals of Islamic education. For this reason, this study tries to explain the concept of maqashid sharia and its implications for Islamic education by using a qualitative approach that is library research. The conclusion of this study, it was found that the relevance of maqashid sharia to Islamic education can be seen in the concept of mabadi al-Khamsah or ushulul al-Khamsah described by al-Ghazali in the form of: (hifdz al-din) maintaining religion, maintaining the soul (hifdz al-nafs) maintain the soul, (hifdz-'aql) maintain the mind, (hifdz al-nasl) maintain offspring, and (hifdz al-maal) maintain property. So that the implications can be seen in the formulation of the goals of Islamic education, namely maintaining and developing the spiritual and physical aspects of students to be able to achieve benefits in their lives.